ORGANIZATIONAL CHANGE AT UNIVERSITY FOR REACHING THE STRATEGIC DEVELOPMENT GOAL - Alexander O. Grudzinskiy; Evgeniy V. Chuprunov (Высшее образование в России)
The paper presents the case study of strategic organizational change in Lobachevsky State University of Nizhni Novgorod, a participant of the «5-100 Program». Key strategic objectives and technologies for organizational change of UNN over the past quarter century are described. The main result of the «soft» restructuring of UNN based on the project-oriented approach is formation of the project-oriented university without destruction of its basic departments. The flexible, mobile and dynamic structure has been created as an additional subdivision to fit the market demand for massive higher education. At the same time the basic university structure continued its development. A description of the main elements (strategic initiatives) of the «roadmap» for UNN's global competitiveness enhancement is given.